Design and Implementation of Model Predictive Control for Parallel Distributed Energy Resource in Islanded AC Microgrids - Khan, Hussain Sarwar; Kumar, Jagdesh; Kauhaniemi, Kimmo (IEEE, 2022)
This study proposes the voltage control strategy for distributed energy resource (DER) in islanded AC microgrids (MG). Typically, AC MG can maintain a constant voltage at the point of common coupling (PCC) as well as perform power-sharing among the DERs. However, linear controllers have several restrictions such as slow transient response, poor disturbance rejection capability etc. Therefore, this study presents an FCS-MPC for a DER with effective voltage regulation capability. The investigated work demonstrates excellent steady-state performance, a low computational burden, better response under transients and have low switching frequency as compared to linear control. First, the benefits of FCS-MPVC for single DER has been studied, then the same topology along with droop control is employed for multiple DERs in AC MG to serve the load. Droop control shows improved power-sharing among the DERs. The performance of the proposed control technique is demonstrated through MATLAB/Simulink simulations for single DG and AC MG under linear, non-linear loading conditions.
Keywords: Distributed Energy Resource (DER) Model Predictive Control (MPC); Primary Control of MG; fi=Sähkötekniikka|en=Electrical Engineering|